The biology, fishery and development of seed production technology of blue swimming crab, portunus pelagicus (Linnaeus, 1766) - Mhd. Ikhwanuddin, Polity @ Abdullah (Universiti Malaysia Sarawak (UNIMAS), 2007)
The study was conducted to determine the biological information and fishery statistics of mud crab, genus Scylla in selected mangrove ecosystems within East Malaysia. The main study site was the Sematan mangrove forest with three other minor study sites; Brunei Bay, Marudu Bay and the Island of Banggi. The important biological information and fishery statistics on mud crab examined was; the size at maturity and mating for both crab sexes; the gonadal development including the annual breeding periodicity and fecundity of the female crabs; the crab distribution, the crab home range and the crab natural growth rate within the mangrove ecosystem; the crab movement within the mangrove ecosystem; the crab population size; and the taxonomic status, carapace width-weight relationship, monthly size and species distribution, sex ratio and fishing catch per unit effort of the mud crabs sampled from the Sematan mangrove forest. For other study sites, data such as taxonomic status, carapace width-weight relationship, monthly size and species distribution, sex ratio and fishing catch per unit effort of the mud crabs was also examined. The recent taxonomic work by Keenan et al., (1998) was used to determine the mud crab species within the study.